Interleukin-1 Receptor Blockade in Perinatal Brain Injury - Rosenzweig, Jason M.; Lei, Jun; Burd, Irina (Frontiers in Pediatrics, 2014)
Interleukin-1 (IL-1) is a potent inflammatory cytokine that can be produced by a variety of cell types throughout the body. IL-1 is a central mediator of inflammation and response to infection and the role of IL-1 signaling in adult and pediatric brain injury is becoming increasingly clear. Although the mechanisms of IL-1 expression are largely understood, the downstream effects and contributions to excitotoxicity and oxidative stress are poorly defined. Here, we present a review of mechanisms of IL-1 signaling with a focus on the role of IL-1 in perinatal brain injury. We highlight research models of perinatal brain injury and the use of interleukin-1 receptor antagonist (IL-1RA) as an agent of therapeutic potential in preventing perinatal brain injury due to exposure to inflammation.